Charlotte's web [videorecording (DVD)] - White, E. B. (Elwyn Brooks), 1899-1985; Nichols, Charles A.; Takamoto, Iwao; Gibson, Henry; Reynolds, Debbie; Lynde, Paul; Moorehead, Agnes, 1900-1974 (Full screen DVD collection, 2001)
Charlotte the spider teaches Wilbur the pig, Templeton the rat and the other barnyard animals lessons on friendship, trust and love.